Pengaruh Kompetensi, Komunikasi dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT. Pertamina Lhokseumawe - Likdanawati Likdanawati; Hamdiah Hamdiah; Ulfa Yuana (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
This study analyzed the influence of Competence, Communication, and Organizational Commitment on Employee Performance at PT. Pertamina Lhokseumawe. This study used primary data from distributing questionnaires to all respondents. The samples were 65 respondents selected using the Census sampling method. This study used multiple linear regression analysis methods. The results partially stated that Competence, Communication, and Organizational Commitment positively and significantly influenced Employee Performance. Simultaneously, Competence, Communication, and Organizational Commitment significantly influenced Employee Performance.